Prevalence of class-I, class-II and class-III obesity in Australian adults between 1995 and 2011–12. Issue 6 (November 2015) - Keating, Catherine; Backholer, Kathryn; Gearon, Emma; Stevenson, Christopher; Swinburn, Boyd; Moodie, Marj; Carter, Rob; Peeters, Anna
Summary: Objective: To compare the prevalence of class-I, II and III obesity in Australian adults between 1995, 2007–08 and 2011–12. Methods: Prevalence data for adults (aged 18+ years) were sourced from customised data from the nationally representative National Nutrition Survey (1995), the National Health Survey (2007–08), and the Australian Health Survey (2011–12) conducted by the Australian Bureau of Statistics. Obesity classifications were based on measured height and weight (class-I body mass index: 30.0–34.9 kg/m 2, class-II: 35.0–39.9 kg/m 2 and class-III: ≥40.0 kg/m 2 ). Severe obesity was defined as class-II or class-III obesity. Results: Between 1995 and 2011–12, the prevalence of obesity (all classes combined) increased from 19.1% to 27.2%. During this 17 year period, relative increases in class I, II and III obesity were 1.3, 1.7 and 2.2-fold respectively. In 2011–12, the prevalence of class I, II and III obesity was 19.4, 5.9 and 2.0 per cent respectively in men, and 16.1, 6.9 and 4.2 per cent respectively in women. One in every ten people was severely obese, increasing from one in twenty in 1995, and women were disproportionally represented in this population. Obesity prevalence increased with increasing levels of area-level socioeconomic disadvantage, particularly for the more severely obese classes. Severe obesity affected 6.2% and 13.4% in the least and most disadvantaged quintiles respectively. Conclusion: Over the last two decades, there have been substantial increases in the prevalence of obesity, particularly the more severe levels of obesity. This study highlights high risk groups who warrant targeted weight gain prevention interventions.